Global Public Health Feasibility: Digital Dentistry in Geriatric Population - Saleh, Merna Amr (AUC Knowledge Fountain, 2026)
Oral health is a critical yet often overlooked determinant of well-being among older adults in Egypt, where mobility limitations, geographic barriers, and low awareness of preventive practices exacerbate dental disparities. DentalPal, a teledentistry-based mobile application, was developed to provide older adults with remote dental consultations, oral hygiene advice, and triage guidance. The platform enables users to submit oral photographs or radiographs for assessment, seek second opinions, and initiate follow-up chats directly with the healthcare provider. This flexible design allows users to access dental consultations on demand while ensuring continuity of care The question that guided this study was how older adults perceive and interact with teledentistry services? Hence, our study evaluates DentalPal, a culturally adapted, bilingual (Arabic/English) teledentistry and mHealth platform designed to deliver online dental consultations, personalized oral hygiene guidance, educational videos, oral behavioral reminders, and proximity-based clinic access. DentalPal combines principles of geriatric dentistry, preventive care, and digital health innovation to overcome barriers faced by older adults while generating high-resolution data for precision public health research. 100 users registered on the mobile application (DentalPal), 83 of whom answered the post-intervention E-questionnaire measuring the satisfaction rate among different domains such as speed of response, helpfulness of the information provided, ease of use of the mobile application, likelihood for future use, and whether their dental concern 100% solved through this online platform or still a dental clinic visit is needed. Our results demonstrated that males and females gave very similar ratings across all questionnaire domains, notably independent samples t-tests indicated no statistically significant differences between males and females in any domain (all p > 0.05). In other words, DentalPal is perceived similarly and positively by both male and female participants, supporting the feasibility of the intervention and its potential acceptability for broader use. By applying ANOVA test, our results showed that no statistically significant differences were observed across age groups for any of the evaluated domains (all p > 0.05). Specifically, the F-values ranged between 0.640 and 2.435, with corresponding significance levels between 0.094 and 0.530, suggesting that users of different age groups generally shared comparable perceptions of the app’s performance and usability. Clearly, these findings indicate that DentalPal was consistently rated positively across all age groups, further supporting its accessibility and appeal to diverse user demographics, including older adults, who are the primary target population of this study. Our descriptive findings showed that the majority of DentalPal’s users are females with most users aged 65 years or older, highlighting our target population. Furthermore, improvements were noticed with regards to the acceptability to the oral hygiene and dental advice, better understanding of dental issues and treatment options among the older adults, increased adherence to oral hygiene practices (e.g., denture cleaning, water flosser and soft toothbrush use, mouthwash application), and enhanced user empowerment, which aligns with the high satisfaction ratings reported across several questionnaire domains . Notably, caregiver involvement played a pivotal role in mitigating digital literacy barriers, particularly when users in this age group encountered challenges in using the technology. Also, Participants presented with a broad spectrum of dental complaints, most frequently routine check-ups and periodontal diseases, reflecting diverse oral health needs among older adults. Most participants also reported at least one chronic condition, predominantly hypertension, high cholesterol, and diabetes. Statistical analysis revealed significant associations between age and both medical conditions and family history, indicating that these variables varied across age groups. This coexistence of oral and systemic conditions underscores the need for a more holistic understanding of older adults’ health, where future research can further explore how systemic diseases and oral health are interrelated. In this context, DentalPal effectively supported initial assessments and remote guidance: the majority of participants (59, 71.1%) were managed exclusively through teledentistry—receiving oral hygiene instructions, denture-cleaning guidance, and advice on maintaining gingival health—while 24 participants (28.9%) required in-person dental care. Even among those referred to clinics, the platform enabled comprehensive preliminary diagnoses and directed users to nearby dental facilities based on their geographic location, thereby saving time, effort, and resources, particularly for those with mobility limitations. Additionally, the app’s customized push notifications—serving as personalized reminders to use mouthwash or clean dentures with Corega tablets—reinforced adherence to oral hygiene practices and sustained engagement over time. Extending beyond the clinical scope, DentalPal intervention underscores that culturally adapted, bilingual teledentistry and mHealth solutions can simultaneously enhance oral health equity, improve preventive care adherence, and empower older adults to manage their dental health remotely. By integrating caregiver support, personalized behavioral reminders, educational videos, and proximity-based clinic guidance, the platform not only addresses traditional access barriers but also generates high-resolution oral–systemic health data, offering precision insights for research. These insights can guide evidence-based decision-making, enabling policymakers, public health authorities, and NGOs to optimize resource allocation, scale interventions cost- effectively, and develop culturally tailored strategies for improving oral health outcomes among underserved older populations in Egypt. In conclusion, this study demonstrates that DentalPal is feasible among older adults’ population in Egypt, showing how scalable, culturally adapted, cost- effective, and precision-oriented digital health intervention it is, offering a replicable model for improving oral health outcomes, advancing equity, and informing health policy and NGO strategies to enhance oral healthcare delivery for older adults in Egypt and similar low- and middle- income settings.